Comparative, real-time in situ monitoring of galvanic corrosion in Mg-Mg2Ca and Mg-MgZn2 couples in Hank's solution. (December 2019) - Liu, Yang; Liu, Xiao; Zhang, Zechuan; Farrell, Nicholas; Chen, Dafu; Zheng, Yufeng
Highlights: Intermetallic compounds Mg2 Ca and MgZn2 were successfully fabricated. Real-time in situ monitoring of the current density, pH value and Mg 2+ concentration of galvanic couples were conducted. Self-forming cathodes on the anode along with anodic reaction were recorded. Corrosion behavior of intermetallic MgZn2 in Hank's solution was evaluated. A mechanism involving galvanic corrosion and corrosion products forming was illustrated. Abstract: The purpose of this study is to comparatively investigate on intermetallic compounds Mg2 Ca and MgZn2 in galvanic corrosion of magnesium alloy by using real-time in situ monitoring techniques. The results indicated Mg2 Ca functioned as an anode with higher anodic current density, higher Mg 2+ concentration and higher pH values than the Mg cathode, while MgZn2 worked as a cathode with a cathodic current density, lower Mg 2+ concentration and higher pH value than the anodic Mg. The results also suggested a corrosion forming mechanism involving solubility product constant ( K sp ) in which Zn-based corrosion products were easier to form than their Mg counterparts.